The association between anxiety and academic performance in children with reading disorder: A longitudinal cohort study. (17th March 2021) - Hossain, Bushra; Bent, Stephen; Hendren, Robert
Abstract : The purpose of this study was to examine the association between anxiety and overall academic performance (AP) in children with reading disorder (RD). This two‐year longitudinal cohort study included 128 participants (aged 7–14 years) with RD. Anxiety symptoms were evaluated using the School Anxiety Scale – Teacher Report for the first year and the eight‐item Spence Children's Anxiety Scale for the second year. AP was assessed by teacher ratings of progress in academic content areas, including reading, writing and math. Teachers completed evaluations every 3 months. We standardized all scores (to z scores). Multivariate linear regression models (adjusting for age, sex and Attention‐Deficit/Hyperactivity Disorder symptoms) assessed the association cross‐sectionally at each timepoint of survey completion. Repeated measures analysis using mixed models assessed the relationship longitudinally. Results from both univariate and multivariate analyses showed anxiety being significantly negatively associated with AP in children with RD, both cross‐sectionally and longitudinally. Importantly, increased anxiety was significantly associated with reduced AP over time within an individual (adjusted β  = −0.22, p  = .002). This lends support to screening for anxiety disorders in children with RD. Future research should examine the directionality of this relationship, potential mediators in the pathway and whether interventions to reduce anxiety increase AP.